2010
DOI: 10.1104/pp.110.163063
|View full text |Cite
|
Sign up to set email alerts
|

Protein Association and Dissociation Regulated by Extension Peptide: A Mode for Iron Control by Phytoferritin in Seeds

Abstract: Most of the iron in legume seeds is stored in ferritin located in the amyloplast, which is used during seed germination. However, there is a lack of information on the regulation of iron by phytoferritin. In this study, soluble and insoluble forms of pea (Pisum sativum) seed ferritin (PSF) isolated from dried seeds were found to be identical 24-mer ferritins comprising H-1 and H-2 subunits. The insoluble form is favored at low pH, whereas the two forms reversibly interconvert in the pH range of 6.0 to 7.8, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…In sea lettuce ferritins, the extension peptide contributes to shell stability and surface hydrophobicity [29]. The removal of the extension peptide in pea seed ferritin both increases protein stability and promotes the reversible dissociation of the mature ferritin protein [30]. The secondary structure of pea seed ferritin is highly similar to that of mammalian ferritin [31].…”
Section: Discussionmentioning
confidence: 99%
“…In sea lettuce ferritins, the extension peptide contributes to shell stability and surface hydrophobicity [29]. The removal of the extension peptide in pea seed ferritin both increases protein stability and promotes the reversible dissociation of the mature ferritin protein [30]. The secondary structure of pea seed ferritin is highly similar to that of mammalian ferritin [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, such protein degradation was not observed in animal ferritins such as HoSF (horse spleen ferritin) and HuHF (human H-chain ferritin) under the same experimental conditions. Interestingly, no protein degradation occurs upon removal of the EP from PSF and SSF (Fu, Deng, Yang, Masuda, Goto, Yoshihara, & Zhao, 2010;Yang, Fu, Li, Leng, Chen, & Zhao, 2010). These findings demonstrated that phytoferritin degradation comes from the EP, a specific domain only located in plant ferritin, but not from any contaminants such as various proteases.…”
Section: Comparison Of the Stability Of Bbsf And Other Plant Ferritinmentioning
confidence: 85%
“…Additionally, similar results were obtained with other buffers, such as Mops or Mes in the 6.0-7.5 pH range (results not shown), and protein samples from three different protein preparations/purifications, suggesting that the observed degradation is not sample/buffer/pH dependent. In contrast to BBSF, PSF began to degrade at the 5th day to a great extent, and the degree of its degradation is much larger as compared to that of BBSF (Yang, Fu, Li, Leng, Chen, & Zhao, 2010). Similar to PSF, SSF is also unstable and the degree of its protein degradation is likewise much stronger than that of BBSF.…”
Section: Comparison Of the Stability Of Bbsf And Other Plant Ferritinmentioning
confidence: 86%
See 2 more Smart Citations